Implementasi Peraturan Hukum dan Upaya Represif yang Dilakukan Untuk Menangani Kasus Pelanggaran HAM di Indonesia - Muhammad Syahru Ramadhan; Rayhan Algazy Wenanda Asyraf; Rezha Ferdiansyah; Dimas Dwi Arso (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This study explores the positive legal perspective that exists in Indonesia on human rights violations. (HAM). As a state of law, Indonesia has a responsibility to deal with various issues related to the public interest, including human rights violations. The findings can be concluded that the legal protection of human rights in Indonesia is naturally contained in the values of the Pancasila before the formation of the specific legal substance regarding human rights. With the method of normative jurisprudence research, this article is titled Implementation of the Law Regulations and Repressive Efforts to Deal with the Cases of Human Rights Violations in Indonesia by the process of collection of literary material through scrutiny, analysis, and systematic compilation of findings. The aim of this study is to examine in depth how the law is applied to cases of human rights violations in Indonesia as well as what the government is doing as a repressive effort to resolve human rights cases in Indonesia. The findings can be summarised by the fact that every country continues to strive to enforce human rights through different systems and actions, including Indonesia. In Indonesia, human rights issues are dealt with through various methods, including consultation, negotiation, media, and consultation. Governments should focus on dealing with the needs and conditions of the people, not just legal issues. Human rights issues in various regions are dealt with through various strategies, such as national and international mechanisms, the Commission on Human Rights, non-judicial machinery, and the Indonesian Human Rights Commission.